Design of Novel Formwork System and Development of Numerical Model for Comparison between Formwork Systems - El Sayed, Ahmed Yehia Abdel Aziz (AUC Knowledge Fountain, 2026)
The formwork industry has witnessed major breakthroughs in the last decades. However, they required huge amount of materials leading to negative environmental impacts. Also, the commercially available systems have big number of accessories and requires the extensive use of units to cover the areas to be poured. There was an attempt to target all these disadvantages by introducing the Funicular Arched Steel Truss (FAST) system. However, this system had its own drawbacks, and this is why the researcher introduced an extendable version named the “Extendable Funicular Arched Steel Truss (EAST) system.” To reach the final version of the EAST design, the researcher carried out structural analysis and tested the system in the lab to understand its structural behavior. The EAST system has proved its feasibility to be an alternative to the commercially available systems as it can support up to 7 tons, has extendibility features due to its structural soundness, allows for movement beneath the system and has low cost. Further, a numerical model was developed to allow for designing and carrying out quantity take off to calculate cost and weight of five types of formwork systems: traditional system, MULTIFLEX, frames, FAST and EAST systems. The numerical model was validated and verified using villa floor plan and proved its reliability. Two-way ANOVA was carried out and proved that the cost and weight of the formwork system is significantly impacted by the formwork type and the area of the floor plan used upon the fixation of the floor plan shape.